The academic performance of orphaned primary school learners aged between eight and ten years in Mankweng Circuit : Limpopo Province - Magampa, Agnes Randy Mmakotsedi (University of Limpopo (Turfloop Campus), 2014)
The study investigated the academic performance of orphaned primary school learners between the ages of eight and ten in Mankweng circuit. The study used both quantitative and qualitative methods. The quantitative component of the study included the sampling of 200 learners from ten schools in Mankweng circuit. One hundred learners formed the experimental group (orphans) whilst another hundred were placed in the comparison group (non-orphans). Availability and quota sampling was used for sampling the experimental group and simple random sampling was used to sample the comparison group. Four learning areas chosen for the study include Sepedi, Numeracy, English and Lifeskills. In all learning areas, it was found that the comparison group fell within level 2 (50-69) area whilst the experimental group fell within level 1 (0-49) area suggesting that the comparison group is performing better than the experimental group. The qualitative component of the study involved sampling ten educators from ten sampled primary schools in Mankweng Circuit, i.e. one educator per school. The main theme that emerged from these transcripts was the educators’ view that orphaned children tend to perform poorly at school when compared to non-orphaned children. Furthermore, the educators were of the view that orphaned children are more likely to show poor grades, lack of concentration and inability to write schoolwork when compared to non-orphans. The educators were also of the view that orphaned children were more likely to display behavioural and emotional problems when compared to non-orphans. Educators also suggested that guardians of orphaned learners are not coping well, and as such, are unable to adequately attend to the needs of these children. In conclusion, interventions at school, government as well as community levels are suggested. A suggestion is also made regarding the support that should be provided for grandparents (guardians) who tend to be drained as a result of having to look after orphaned children.
Thesis (M.A. ( Research Psychology)) --University of Limpopo, 2014
Keywords: Mankweng Circuit; Academic performance; Orphans; Primary school learners; Academic achievement; School improvement programs; Teaching